KONTEKSTUALISASI AYAT-AYAT INFȂQ DALAM TAFSIR AL-MUNIR KARYA PROF. DR. WAHBAH ZUHAILY - Jamil, Ahmad (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2021)
The discussion of the concept of infaq and its derivatives, namely zakat and shadaqoh, is a very important issue. Many people assume that people who invest their wealth will decrease or even run out. In fact, if the utilization and utilization of infaq and its derivatives are optimized, it will boost the economy of the people and be able to alleviate poverty in Muslims in particular. So from that this literacy tries to provide an understanding of the contextualization of the infaq verses in the interpretation of Al-Munir by Prof. Dr. Wahbah Zuhaily. This research uses literature methods and literacy studies from classical and contemporary scholars who are experts in their fields. The results of this study answered with certainty the nature of infaq, zakat and shadaqah along with the secrets and great wisdoms in them according to the instructions of the Al-Qur'an, especially those described by Prof. Dr. Wahbah Zuhaily in Tafsir Al-Munir